Mental health literacy: what do Nigerian adolescents know about depression? - Aluh, Deborah O. (Int J Ment Health Syst, 2018)
BACKGROUND: Depression is a leading cause of disability and has been projected to become the 2nd most burdensome disease by the year 2020; depression has also been found to be the strongest single risk factor for attempted or completed suicides. Adolescent-onset mood disorders are frequently unrecognized or misdiagnosed and often go untreated. While there is a growing literature on the mental health literacy of adults, there has not been a parallel interest in the mental health literacy of young people in Nigeria. METHODS: The study was a cross-sectional descriptive survey conducted among students of a Federal Government College (high school) in south-east Nigeria. All consenting students in the senior secondary classes (grades 10–12) were recruited, making a total of 285 participants. The participants were presented with the ‘friend in need’ questionnaire designed to elicit the participants’ recognition of the disorder depicted in two vignettes and their recommendation about the appropriate source of help-seeking. One vignette was of a clinically depressed case while the other vignette was about a girl undergoing normal life crisis. RESULTS: Out of the 285 students recruited into the study, 277 questionnaires were adequately completed indicating a response rate of 97.2%. A total of 4.8% (n = 13) participants correctly identified and labelled the depression vignette. Only four respondents (1.5%) recommended professional help from a Psychiatrist or Psychologist. Insomnia was the most identified symptom of distress for depression (17.1%). Females demonstrated higher mental health literacy, in terms of their ability to correctly label the depression vignettes, their expression of greater concern over a depressed peer than males, their expectation that depression requires a longer recovery than normal teenage problems and in their ability to identify individual symptoms of depression. Family and friends were the most recommended source of help. CONCLUSION: Mental health literacy was abysmally low amongst the adolescents surveyed. There’s an urgent need to increase mental health awareness in Nigeria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13033-018-0186-2) contains supplementary material, which is available to authorized users.